The Effect of Planning, Implementation, and Supervision of Village Funds on the Economic Empowerment of Village Communities - Sefnat Aristarkus Tang; Yustina Maro (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to determine the effect of planning, implementation, and monitoring of Village Funds on economic empowerment Village community in Taramana Village, Northeast Alor District, Alor Regency, either partially or simultaneously. The population in this study was 14 people. The research sample was carried out using a saturated sample. Data collection techniques are observation, interviews, questionnaires, and literature study. The data analysis method used is validity test, reliability test, and multiple linear regression. The results showed that all statements in the questionnaire were declared valid. They had an r-value count of more than 0.300 and all variables were declared reliable because they had values Cronbach's Alpha of more than 0.600. Partially the planning variable has a significant t-test value of 0.000; the implementation variable has a t-test significance value of 0.000, and the control variable has a t-test significance value of 0.000 where the t-test significance value of each independent variable is smaller than the alpha value (∂=0.05) so that partially all independent variables have a significant effect on the dependent variable. Meanwhile, simultaneously the significance value of the F test is 0.000 where this value is smaller than the alpha value (∂ = 0.05) so that together all the independent variables in this study affect the dependent variable.